PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MELALUI LIVEWORKSHEET PADA PEMBELAJARAN BAHASA INDONESIA SMP - Prihatin Sri Mulyani; Mukti Widayati; Benedictus Sudiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop an Interactive Digital Worksheet called "Liveworksheet" and assess its feasibility and practicality as a learning tool for Indonesian language in junior high school (SMP). The study employs a research and development (R&D) method, utilizing the Borl and Gell development framework consisting of six steps to create the Interactive Digital Worksheet (Liveworksheet). The six steps are: identifying potential and problems, data collection, product design, design validation, design revision, and product testing. The subjects of the study included a subject matter expert, a media expert, two Indonesian language teachers from SMP (junior high school), and ninth-grade students from SMP Negeri 2 Miri, Sragen Regency. Data were collected through the feasibility questionnaire for the Liveworksheet, observations, and documentation. Data analysis employed quantitative descriptive statistics. The result of this research is an Interactive Digital Worksheet called "Liveworksheet" for students. The media feasibility, validated by the subject matter expert and media expert, received an average score of 78, with a percentage of 83.55%, indicating that the developed media is considered "feasible." Practicality validation conducted by teachers and students yielded an average score of 100, with a percentage of 83.33%, demonstrating that the Digital Liveworksheet is practical for enhancing student motivation in learning at SMP Negeri 2 Miri. This research suggests that teachers should consider developing Interactive Digital Worksheets (Liveworksheets) for other subjects as well.